2021
DOI: 10.1186/s10194-021-01363-y
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing monoclonal antibodies targeting CGRP pathway after one-year treatment: an observational longitudinal cohort study

Abstract: Background Monoclonal antibodies anti-calcitonin gene-related peptide (mAbs anti-CGRP) pathway are effective and safe on migraine prevention. However, some drug agencies limited these treatments to one year due to their high costs. This study aimed at evaluating the effect of discontinuing mAbs anti-CGRP on monthly migraine days (MMDs) and disability in high-frequency episodic (HFEM) and chronic migraine (CM) patients. Methods This observational lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
(29 reference statements)
6
35
0
8
Order By: Relevance
“…This data is relevant for clinical practice as most patients treated with a CGRP(-R) mAb in Europe undergo a drug holiday after 6–12 months as recommended by national and international guidelines, or even forced by the healthcare systems of some countries [ 14 , 15 , 19 ]. Recent studies have focused on migraine progression after treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This data is relevant for clinical practice as most patients treated with a CGRP(-R) mAb in Europe undergo a drug holiday after 6–12 months as recommended by national and international guidelines, or even forced by the healthcare systems of some countries [ 14 , 15 , 19 ]. Recent studies have focused on migraine progression after treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Gantenbein et al, half of patients reached after three months of treatment pause a number of MMD comparable to the baseline phase [ 15 ]. Vernieri et al also reported a gradual increase of MMD following cessation of treatment with erenumab and galcanezumab: After three months of drug holiday the 50% responder rates decreased from > 70% to < 30% [ 19 ]. Similarly, in the parent study of this analysis, we showed a significant increase of migraine frequency over time after CGRP(-R) mAbs treatment cessation [ 17 ], which is also observed in this subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the frequency of migraine attacks decreases, patients are more likely to lead a healthier lifestyle and be less impacted by the fear of pain and psychosocial stress [ 33 ]. This indirect advantage exerted by mAb targeting the CGRP pathway is also supported by the no-return to the baseline condition after 3 months of suspension [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the majority of patients with chronic migraine reverted to episodic migraine after one year of treatment, data collected by these authors demonstrated that, in most patients, the therapeutic effect does not persist after anti-CGRP mAb discontinuation. For this reason, anti-CGRP mAb cannot be considered disease-modifying treatments, at least not after a one-year period of use [ 75 ]. It would be necessary to observe the clinical course of patients withdrawing the therapy with these biological drugs after longer treatment periods.…”
Section: Discussionmentioning
confidence: 99%